The Utility of Endoscopic Biopsies in Patients with Normal Upper Endoscopy - Anouar Teriaky; Abdullah AlNasser; Carolyn McLean; James Gregor; Brian Yan (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Upper endoscopy is a valuable tool in the workup of gastrointestinal (GI) complaints. The purpose of this study is to determine cost and yield of taking biopsies in a normal upper GI tract. Methods. This is a retrospective study where all upper GI biopsies were identified between May 2012 and April 2013, at a tertiary care center. Clinical, procedural, and pathology reports were reviewed to identify patient demographics, procedure information, and pathology diagnosis. Results. Biopsies of the upper GI tract were taken in 1297 patients with normal upper endoscopies. In patients with normal upper endoscopy, 22% of esophageal, 44% of gastric, and 12% of duodenal biopsies were abnormal. The most frequent abnormality was reflux esophagitis in 16% of esophageal biopsies, chronic gastritis in 23% of gastric biopsies, and increased intraepithelial lymphocytes in 6% of duodenal biopsies. The additional cost for taking biopsies in a normal upper GI tract for a diagnosis of eosinophilic esophagitis was $2963 Canadian (CAD), H. pylori associated gastritis was $1404 CAD, and celiac disease was $3024 CAD. Conclusions. The yield of biopsy in normal upper endoscopy varied with location, but the additional expense can be costly and should be tailored to appropriate clinical situations.